El conflicto político como mecanismo de legitimización de alcaldes provinciales. Análisis de los casos de Arequipa (2002) y Espinar (2012) - Hurtado, Verónica (2015)
In the current Peruvian context, the provincial mayors face serious problems to remain inoffice or to pursue a future political race. In this scenario, the social conflicts arise as an alternative for obtaining such legitimacy; however, depending on the type of participation adopted, the mayor could or could not be benefited from such an opportunity. The paper presents an analysis of the participation of those authorities in social conflicts and its effects on his political career.It is argued that the participatory scheme, which provides a clear firmness in support of demands immediately; but, at the same time, the ability to negotiate with the State; would yield the expected political revenue. On the other hand, if the authority is very weak or very radical, his attempts to use the social conflict to their advantage could fail. To test this hypothesis, I studied the conflicts of Arequipa in 2002 and Espinar in 2012.